2021
DOI: 10.1109/jtehm.2021.3092559
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Regulatory Changes to Promote Pediatric Device Innovation in the United States: Joint Recommendations From Pediatric Innovator Roundtables

Abstract: The purpose of this report is to provide insight from pediatric stakeholders with a shared desire to facilitate a revision of the current United States regulatory pathways for the development of pediatric healthcare devices. Methods: On August 5, 2020, a group of innovators, engineers, professors and clinicians met to discuss challenges and opportunities for the development of new medical devices for pediatric health and the importance of creating a regulatory environment that encourages and accelerates the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The Federal Drug Administration's Real-World Evidence programme provides a new path to their clearance/approval for device trials in children. The Real-World Evidence programme has demonstrated how existing healthcare systems can collect, store, and curate data that can be utilised 42 bypassing traditional randomised controlled trials, which are costly and pose challenges for complete data collection. Philanthropic organisations such as Enduring Hearts, often in collaboration with dedicated professional societies, such as the Pediatric Heart Transplant Study Group, International Society of Heart Lung Transplantation, and the American Heart Association, are providing important research funding for paediatric heart transplant recipients.…”
Section: Section 3 the Challenge For Paediatric Heart Transplantation...mentioning
confidence: 99%
“…The Federal Drug Administration's Real-World Evidence programme provides a new path to their clearance/approval for device trials in children. The Real-World Evidence programme has demonstrated how existing healthcare systems can collect, store, and curate data that can be utilised 42 bypassing traditional randomised controlled trials, which are costly and pose challenges for complete data collection. Philanthropic organisations such as Enduring Hearts, often in collaboration with dedicated professional societies, such as the Pediatric Heart Transplant Study Group, International Society of Heart Lung Transplantation, and the American Heart Association, are providing important research funding for paediatric heart transplant recipients.…”
Section: Section 3 the Challenge For Paediatric Heart Transplantation...mentioning
confidence: 99%
“…Other studies such as another report using a computational study of fluid dynamics showing that the Avalon performed better than the OriGen catheter, with lower recirculation fraction than the OriGen catheter also found that further optimization of the Avalon catheter could be achieved (15). In the case of small populations, there is a need for decreasing barriers and increasing financial and nonfinancial incentives for more active device innovation based on such reports and studies (16). The Cresent cannula, a new bicaval-right atrial catheter for V-V ECMO, was recently introduced, and initial reports in adults have been favorable but experience in neonates have not been published (17).…”
mentioning
confidence: 99%